2022
DOI: 10.1108/intr-05-2021-0294
|View full text |Cite
|
Sign up to set email alerts
|

Fake news on the internet: a literature review, synthesis and directions for future research

Abstract: PurposeThe extensive distribution of fake news on the internet (FNI) has significantly affected many lives. Although numerous studies have recently been conducted on this topic, few have helped us to systematically understand the antecedents and consequences of FNI. This study contributes to the understanding of FNI and guides future research.Design/methodology/approachDrawing on the input–process–output framework, this study reviews 202 relevant articles to examine the extent to which the antecedents and cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 216 publications
(647 reference statements)
0
12
0
2
Order By: Relevance
“…There is also a remarkable amount of disagreement over the classification of the term fake news in the research literature, as well as in policy (de Cock Buning 2018;ERGA 2018ERGA , 2021. Some consider fake news as a type of misinformation (Allen et al 2020;Singh et al 2021;Ha et al 2021;Shao et al 2018b;Di Domenico et al 2021;Sharma et al 2019;Celliers and Hattingh 2020;Klein and Wueller 2017;Potthast et al 2017;Islam et al 2020), others consider it as a type of disinformation (de Cock Buning 2018) (Bringula et al 2022;Baptista and Gradim 2022;Tsang 2020;Tandoc Jr et al 2021;Bastick 2021;Khan et al 2019;Shu et al 2017;Nakov 2020;Shu et al 2020c;Egelhofer and Lecheler 2019), while others associate the term with both disinformation and misinformation (Wu et al 2022;Dame Adjin-Tettey 2022;Hameleers et al 2022;Carmi et al 2020;Allcott and Gentzkow 2017;Zhang and Ghorbani 2020;Potthast et al 2017;Weiss et al 2020;Tandoc Jr et al 2021;Guadagno and Guttieri 2021). On the other hand, some prefer to differentiate fake news from both terms (ERGA 2018;Molina et al 2021;ERGA 2021) (Zhou and Zafarani 2020;…”
Section: Definitions Of Fake Newsmentioning
confidence: 99%
“…There is also a remarkable amount of disagreement over the classification of the term fake news in the research literature, as well as in policy (de Cock Buning 2018;ERGA 2018ERGA , 2021. Some consider fake news as a type of misinformation (Allen et al 2020;Singh et al 2021;Ha et al 2021;Shao et al 2018b;Di Domenico et al 2021;Sharma et al 2019;Celliers and Hattingh 2020;Klein and Wueller 2017;Potthast et al 2017;Islam et al 2020), others consider it as a type of disinformation (de Cock Buning 2018) (Bringula et al 2022;Baptista and Gradim 2022;Tsang 2020;Tandoc Jr et al 2021;Bastick 2021;Khan et al 2019;Shu et al 2017;Nakov 2020;Shu et al 2020c;Egelhofer and Lecheler 2019), while others associate the term with both disinformation and misinformation (Wu et al 2022;Dame Adjin-Tettey 2022;Hameleers et al 2022;Carmi et al 2020;Allcott and Gentzkow 2017;Zhang and Ghorbani 2020;Potthast et al 2017;Weiss et al 2020;Tandoc Jr et al 2021;Guadagno and Guttieri 2021). On the other hand, some prefer to differentiate fake news from both terms (ERGA 2018;Molina et al 2021;ERGA 2021) (Zhou and Zafarani 2020;…”
Section: Definitions Of Fake Newsmentioning
confidence: 99%
“…Pasauliniu mastu galima identifikuoti bent keliolika skirtingų melagingų naujienų tyrimo krypčių (kūrimo motyvacija; kas lemia jų plitimą; melagingų naujienų požymiai ir t. t., žr. Wu et al, 2022), Lietuvoje tyrimo laukas kiek siauresnis: analizuojama kūrimo ar platinimo motyvacija (Wilson & Maceviciute, 2022), melagingų naujienų grėsmė Lietuvos nacionaliniam saugumui informacinio karo kontekste (Denisenko, 2020), melagingų naujienų plitimo prevencija didinant medijų raštingumą (Šuminas & Jastramskis, 2020) ir pan. Tačiau pastebėtina, kad dauguma tyrimų, kurie yra atlikti siekiant suprasti, kodėl žmonės patiki melagingomis naujienomis, yra grįsti prielaida, kad patikėjimo procesai yra vienodi ir aplinkybės, kuriomis žmonės priima sprendimus apie naujienos tikrumą, juos paveikia vienodai (pvz., žr.…”
Section: įVadasunclassified
“…Kaip jau buvo minėta, susidūrimas su melagingomis naujienomis gali turėti įvairių neigiamų pasekmių (Rocha et al, 2021). Nepaisant to, kad melagingos naujienos gali būti kuriamos ir platinamos įvairiais tikslais ir būti susijusios su įvairiomis temomis (Wu et al, 2022), išsiskiria dvi temos -politinė ir sveikatos.…”
Section: Galimos Patikėjimo Melagingomis Naujienomis Pasekmės: Vakcin...unclassified
“…Therefore, equipping individuals with the necessary tools to identify FN is crucial (Zhang & Ghorbani, 2020 ). However, the usage of these necessary tools, especially cognitive ones, to combat FN is not investigated sufficiently (Machete & Turpin, 2020 ; Wu et al, 2022 ) and there is a clear need for other studies investigating what can be done and how these tools can be used to combat against FN (Au et al, 2021 ). Previous literature has showed that CT and NML, which can also be seen as a survival kit for this century, are two of the most essential cognitive tools that can be used by individuals to protect themselves against FN on SM.…”
Section: Introductionmentioning
confidence: 99%